Evaluating the Utility Core in the Prefabricated Building Industry – past, present and future - Carbone, Carlo; Eid Mohamed, Basem (Enquiry The ARCC Journal for Architectural Research, 2017)
Harnessing, distributing, tempering and supplying water, heat and power in a building produces its share of design, technical and coordination issues. Specifically, the relationship between hygiene and cooking functions and architecture has been underscored by even the most ancient civilizations as these services give a building its potential to serve and showcase architecture's hospitality. The relationship between services and architectural space has long challenged designers and manufacturers to streamline their piecing together. Throughout construction history and modern architecture in particular the wet service core or utility core sought to organize an efficient way of zoning services, their production and construction integration; The utility core epitomized this rationalization within a self-contained engine-like device positioned to serve the entire dwelling. This paper proposes an extensive review of literature and practical exploration in order to detect new potentials for designing integrated, technology-driven, flexible and adaptable prefabricated utility cores for today's industry. The core was intended as a hub accommodating mechanical and technological equipment; electrical services, plumbing fixtures, water supply, drain, waste, vent piping, telephone cables, and easy connections to site infrastructure. Today's techniques and building information modeling allows the core to be redefined in relation to multiple scales and various organizational possibilities with regard to space/function connections. Further an adaptable core articulated to the «open building» theoretical framework of layering systems to avoid entanglement and to maximize durability, can be part of a comprehensive strategy to enable customization. The vast amount of literature and precedents contribute to a robust historic narrative of two distinct approaches of architectural rhetoric and industrial production.  This paper will endeavor to illustrate this narrative and evaluate the potentials for achieving broader application.